IN VITRO ANTIOXIDANT AND IN VIVO ANTIDIABETIC ACTIVITY OF TWO POTENTIAL PROBIOTIC ENTEROCOCCUS SPP. ON ALLOXAN-INDUCED DIABETIC RATS - RAJPUT, KAMNI; CHANDRA DUBEY, RAMESH (Asian Journal of Pharmaceutical and Clinical Research, 2021)
Objective: In vitro antioxidant activity, in vivo antidiabetic property and intestinal attachment by two potential probiotic bacterial strains, namely, Enterococcus faecium and Enterococcus hirae were studied using albino rats. Methods: Antioxidant the activity was assessed using 2,2-Diphenyl-1-picrylhydrazyl radicals scavenging assay. Alloxan was administered intraperitoneally to induce diabetic conditions in experimental rats. Animals were treated with oral administration of Enterococcus spp., such as E. faecium, and E. hirae isolated from goat and sheep milk. The control animal group received normal saline for the same days. Glibenclamide drug was used as a positive control against probiotic bacterial cells. Results: However, administration of probiotic bacterial strains E. faecium and E. hirae, in albino rats significantly (p<0.05) at varying doses lowered blood glucose levels in diabetic rats as compared to the diabetic control group. Both the species of Enterococcus increased the bodyweight of experimental rats. However, E. faecium was the best antidiabetic strain having the antioxidant activities also in comparison to E. hirae. The attachment of probiotic bacterial cells E. faecium on the rat’s intestine wall against pathogens was examined. Furthermore, E. faecium showed its aggregation with pathogens by attachment of the intestines of albino rats. This showed that both the bacterial strains exhibited in vivo antidiabetic effect. Conclusion: The results of this study showed that probiotic bacteria possess antioxidant, antidiabetic activities, and attachment of intestine.